Flg22-Triggered Immunity Negatively Regulates Key BR Biosynthetic Genes - Jiménez-Góngora, Tamara; Kim, Seong-Ki; Lozano-Durán, Rosa; Zipfel, Cyril (Frontiers in Plant Science, 2015)
In plants, activation of growth and activation of immunity are opposing processes that define a trade-off. In the past few years, the growth-promoting hormones brassinosteroids (BR) have emerged as negative regulators of pathogen-associated molecular pattern (PAMP)-triggered immunity (PTI), promoting growth at the expense of defence. The crosstalk between BR and PTI signalling was described as negative and unidirectional, since activation of PTI does not affect several analysed steps in the BR signalling pathway. In this work, we describe that activation of PTI by the bacterial PAMP flg22 results in the reduced expression of BR biosynthetic genes. This effect does not require BR perception or signalling, and occurs within 15 minutes of flg22 treatment. Since the described PTI-induced repression of gene expression may result in a reduction in BR biosynthesis, the crosstalk between PTI and BR could actually be negative and bidirectional, a possibility that should be taken into account when considering the interaction between these two pathways.